Can street entrepreneurs be Schumpeterian entrepreneurs? The case of food trucks as family firms in an emerging country - Daniele Eckert Matzembacher; Rogério Leite Gonzales; Carlos S. V. Saldanha (Journal of Global Entrepreneurship Research, 2019)
In times of economic downturn, entrepreneurship discourse returns to the forefront. In this context, in Brazil, there is a new economic and social phenomenon going on: street ventures as family firms. Once marginalized and normally related to informal work, now they perform activities in the market that allow them to offer higher quality products and to reach consumers with higher purchasing power. Aiming to better understand the phenomenon, this study explores the main aspects that characterize entrepreneurship, its motivations, knowledge and capacity for innovation. A participant observation was carried out analyzing the operation of 44 food trucks and in-depth interviews were conducted with 11 food trucks owners. Results indicate that, unlike the literature premise, the first entrant food trucks were Schumpeterian entrepreneurs. However, there was a dissemination of knowledge and they lost this condition. As a result, suggestions are presented to these entrepreneurs return to the Schumpeterian condition. This paper advances in theoretical knowledge by identifying that the Schumpeterian innovation of this street entrepreneurship is highly geographic-contextual. It possible can lead to a decrease in the risk of business failure in places in which knowledge is disseminated as innovation.
Keywords: 650; Entrepreneurship; Food trucks; Food sector; Innovation; Knowledge dissemination; Low tech; Schumpeter; Small business